Concepções sobre música e motivações musicais: um estudo qualitativo sobre alunos de um seminário de música sacra - Nata Oliveira Andrade (2007)
The present work has as object the research the conceptions about music, motivations and music expectatives of students of a Sacred Music Seminar. For this study I used qualitative research strategies. These strategies include document collection, participant observations and semi-structured interviews with 22 seminar students during a year and a half. The interpretative analysis of the data revealed categories those results in a profile of the students from a Sacred Music Seminar in relation to their concept about music. The conclusions indicated idiosyncrasies of the social ambient in which they study and forma social group.